Adjusting WiMAX for a Dedicated Surveillance Network - Suherman Suherman; Marwan Al-Akaidi (International Journal of Electrical and Computer Engineering (IJECE), 2013)
WiMAX (Worldwide Interoperability for Microwave Access) devices have been used widely in the market. WiMAX-based video surveillance products have also been available. The acceptance of WiMAX in the market, as well as the availability of WiMAX products, contributes to the possibility of implementing it for dedicated video surveillance application. However, since WiMAX is designed to accommodate various applications with different quality of service (QoS) requirements, WiMAX–based dedicated surveillance network may not achieve optimum performance, as all SSs generate the same QoS requirements. The scheduler cannot implement traffic type priority; therefore, service classification does not work as expected. This paper proposes WiMAX adjustment to transform a multi-purpose WiMAX network into a network dedicated to video surveillance. NS-2 simulations show that the proposed adjustment is able to deliver low delay and high quality video surveillance.DOI:http://dx.doi.org/10.11591/ijece.v3i4.3181